ChemInform Abstract: Microwave‐Ultrasound Simultaneous Irradiation: A Hybrid Technology Applied to Ring Closing Metathesis. Issue 27 (18th June 2015) - Sacco, M.; Charnay, C.; De Angelis, F.; Radoiu, M.; Lamaty, F.; Martinez, J.; Colacino, E.
Abstract A new hybrid microwave‐ and ultrasound‐assisted reactor is developed.